2019
DOI: 10.1002/mgg3.614
|View full text |Cite
|
Sign up to set email alerts
|

A prenatally diagnosed case of Meckel–Gruber syndrome with novel compound heterozygous pathogenic variants in the TXNDC15 gene

Abstract: Background Meckel–Gruber syndrome (MKS) is a well‐known rare disease that can be detected on prenatal ultrasound. Meckel–Gruber syndrome has very heterogeneous etiology; at least, 17 genes have been described in association with MKS. The characteristic findings in fetuses affected by MKS are encephalocele (usually occipital), postaxial polydactyly, and polycystic dysplastic kidneys. However, the association of the TXNDC15 gene with MKS has been reported only once before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…In addition to the polydactyly, we (Table S3). 16 (Table S3). The pathogenic variants in TXNDC15 cause aberrant localization of TMEM67 to the transition zone, reduced number of ciliated cells and abnormal ciliary morphology.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the polydactyly, we (Table S3). 16 (Table S3). The pathogenic variants in TXNDC15 cause aberrant localization of TMEM67 to the transition zone, reduced number of ciliated cells and abnormal ciliary morphology.…”
Section: Resultsmentioning
confidence: 99%
“…TXNDC15 : Thioredoxin Domain‐containing protein 15, encodes a protein thioredoxin fold which intricate in disulfide isomerase activity. Two reports have implicated TXNDC15 in MKS earlier . Shaheen et al, identified two homozygous variants [c.672_686del, c.103 + 1G > A, c.956dup] in TXNDC15 , in three unrelated fetuses with classical features of MKS for the first time .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in TMX5 gene have recently been associated with the development of the Meckel-Gruber syndrome (MKS), a rare perinatally lethal autosomal recessive disease caused by defective ciliogenesis [ 58 ]. Deletions and missense mutations result in the generation of truncated forms of TMX5 that do not localize within primary cilium or periciliary regions as the wild type [ 59 , 60 , 61 ]. Thus, the mis-localization or the premature degradation of TMX5 might correlate with the onset of such ciliopathies.…”
Section: Tmx5 a Natural Trapping Mutant Member Of The Tmx Familymentioning
confidence: 99%
“…Su incidencia es variable, depende de la región geográfica y del origen étnico. 4,5 www.medigraphic.org.mx…”
Section: Introductionunclassified